2021
DOI: 10.1007/s00167-021-06447-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism and racial diversity render bone–implant mismatch inevitable after off-the-shelf total knee arthroplasty: a systematic review and meta-analysis

Abstract: Purpose The purpose of this systematic review and meta-analysis was to investigate the variability in femoral geometric ratios among knees of diferent sexes and races, and to appreciate whether the observed variability is accommodated by commonly implanted total knee arthroplasty (TKA) components. The hypothesis was that the anthropometric studies report considerable variability of femoral geometric ratios among sexes and races. Methods This systematic review and meta-analysis was performed according to the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 64 publications
3
23
0
1
Order By: Relevance
“…Próteses menores não levam a cobertura óssea total com aumento da hemorragia e perda de área de fixação, principalmente cortical. No entanto, os benefícios dos implantes personalizados ainda não foram confirmados [9]. InterAm J Med Health 2022;5:20220224 Neste estudo, calculamos a área de osso exposto em componente femoral subdimensionado.…”
Section: Discussionunclassified
“…Próteses menores não levam a cobertura óssea total com aumento da hemorragia e perda de área de fixação, principalmente cortical. No entanto, os benefícios dos implantes personalizados ainda não foram confirmados [9]. InterAm J Med Health 2022;5:20220224 Neste estudo, calculamos a área de osso exposto em componente femoral subdimensionado.…”
Section: Discussionunclassified
“…According to Beckers et al [ 36 ], men had wider knees (range 108~151%) than women (range 106~146%), and compared to Caucasian knees (range 116~126%), Arabian (range 106~149%) and Indian (range 118~147) knees were wider, while East Asian knees were narrower (range 100~118). This study on Korean men showed knee ASRs of 95~119%, similar to the results of a previous study on Asians [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Off-the-shelf (OTS) TKA can result in implant overhang, malalignment and/ or abnormal kinematics [45]. This can be attributed to the inability of OTS TKA to cover the considerable morphologic variability observed in anthropometric studies [3,4,13]. Custom TKA based on computed tomography (CT) reconstructions has the potential to re-establish native tibial and femoral shapes, and reduce bone-implant mismatch, while restoring constitutional alignment (CA) within predetermined limits to maintain overall phenotype [18][19][20].…”
Section: Introductionmentioning
confidence: 99%